First record of beak deformity in “Pipira-preta” (Tachyphonus rufus) Passeriformes: Thraupidae - Moura, Aloysio Souza de; Macedo, Andrea Soares de; Machado, Felipe Santana; Fontes, Marco Aurélio Leites (Brazilian Journal of Science, 2022)
Bird beak deformities are already well reported on other continents. In American continent, yet these data show a fine line. The beak influences from foraging to genetic transfer to offspring. In Brasil, studies on approximately 35 species of native Passeriformes are described. In this study, the first report of structural deformity in the beak of Tachyphonus rufus was presented. Deformity was observed in both the upper and lower jaws for T. rufus.